AN ASSESSMENT OF THE NON-GRADED SYSTEM BASED ON LEARNERS’ LEARNING SATISFACTION, BEHAVIOR, AND OUTCOMES - Barcelona, Alvin (PEOPLE: International Journal of Social Sciences, 2017)
This study aimed to assess the Non-graded System of a progressive school which advocates self-paced and individualized mode of learning, mastery learning program, and modular approach to learning based on learners’ Learning Satisfaction, Behavior, and Outcomes. A combined evaluation model was used which is Outcome Evaluation with influence of Kirkpatrick’s’ Four Level training evaluation. The concurrent mixed method design was used in gathering and interpreting the answers provided by the respondents. Data gathering tools used include a learning satisfaction survey, school archives, individual interviews, and focused group discussions. For the learning satisfaction, 217 higher level learners were chosen using stratified random sampling and for the learning outcomes, K4-10 Summary of Learners’ Academic Performance (SLAP) of all the learners were included. Results showed that non-graded system causes less academic pressure but gives opportunities to correct mistakes; provides more engaging learning experiences; strengthens independent and individualized learning; offers opportunities for academic advancement and academic freedom; and highlights the advantages of non-existence of grades. In general, the respondents were satisfied with the non-graded system. In terms of learning outcomes, the proportions of the learners who finished their academic requirements for two academic years were very high (94.30%). Moreso, report on periodical accomplishments that focus on the self-paced learning showed that on average, 69.36% of the total learners accomplished the set targets. The identified positive changes in the behavior of the learners as a result of their learning experiences were strengthened self-reliance and self-esteem, improved patience, and appreciation towards studying. However, it was also revealed that there are a number of learners who needed to be more motivated to become more academically productive.